2017
DOI: 10.1159/000455334
|View full text |Cite
|
Sign up to set email alerts
|

Does Braun Anastomosis Have an Impact on the Incidence of Delayed Gastric Emptying and the Extent of Intragastric Bile Reflux Following Pancreatoduodenectomy? - A Randomized Controlled Study

Abstract: Background/Aims: This study investigated the impact of Braun anastomosis on the incidence of delayed gastric emptying (DGE) and on the intragastric bile reflux after pancreatoduodenectomy with Child reconstruction. Methods: Sixty-eight patients who underwent subtotal stomach-preserving pancreatoduodenectomy were included. Patients were randomly assigned to a group with or without Braun anastomosis intraoperatively. Twenty-four-hour intragastric bilirubin monitoring was performed to investigate the extent of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
(25 reference statements)
0
14
0
1
Order By: Relevance
“…Ages, gender mix and BMI were generally comparable between direct comparisons, although the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male-predominant cohort (more than 70 per cent). Most studies were conducted in Asia (16 of 24; 67 per cent) 5 , 35 , 36 , 38–46 , 48 , 50 , 51 , 53 , 10 of which were in Japan 5 , 35 , 36 , 39 , 42 , 44 , 46 , 48 , 50 , 51 . Study characteristics are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ages, gender mix and BMI were generally comparable between direct comparisons, although the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male-predominant cohort (more than 70 per cent). Most studies were conducted in Asia (16 of 24; 67 per cent) 5 , 35 , 36 , 38–46 , 48 , 50 , 51 , 53 , 10 of which were in Japan 5 , 35 , 36 , 39 , 42 , 44 , 46 , 48 , 50 , 51 . Study characteristics are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…1 . The search strategy generated 11 articles [ 4 6 , 11 18 ] that fulfilled the inclusion criteria with a total of 1672 patients (1005 in Braun group and 667 in non-Braun group). The characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It also reduces tension on the anastomosis [ 11 , 12 ]. However, there are limited studies on the effectiveness of Braun enteroenterostomy on DGE following pancreaticoduodenectomy and the results are conflicting [ 4 6 , 11 18 ]. Meta-analysis provides a way to increase statistical power and resolve inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations